A review of educational dialogue strategies to improve academic writing skills. (July 2023) - Schillings, Marlies; Roebertsen, Herma; Savelberg, Hans; Dolmans, Diana
Written feedback plays a key role in the acquisition of academic writing skills. Ideally, this feedback should include feed up, feed back and feed forward. However, written feedback alone is not enough to improve writing skills; students often struggle to interpret the feedback received and enhance their writing skills accordingly. Several studies have suggested that dialogue about written feedback is essential to promote the development of these skills. Yet, evidence of the effectiveness of face-to-face dialogue remains inconclusive. To bring this evidence into focus, we conducted a literature review of face-to-face dialogue intervention studies. The emphasis was on key elements of the interventions and outcomes in terms of student perceptions and other indicators, and the methodological characteristics of the studies. Subsequently, we analysed each selected intervention for the presence of feed-up, feed-back and feed-forward information. Most interventions used all three feedback elements – notably assessment criteria, student feedback, and revision, respectively – and combined lecturer–student as well as student–student dialogue. Students generally perceived the interventions as beneficial; they appreciated criteria and exemplars because they clarified what was expected of them and how they would be assessed. With regard to student outcomes, most interventions positively affected performance. The literature review suggests that feedback dialogue shows promise as an intervention to improve academic writing skills, but also call for future research into why and under which specific conditions face-to-face dialogue is effective.